Spenito and Split ends act redundantly to promote Wingless signaling. - Chang, J.L.; Lin, H.V.; Blauwkamp, T.A.; Cadigan, K.M. (Developmental Biology, 2008)
Wingless (Wg)/Wnt signaling directs a variety of cellular processes during animal development by promoting the association of Armadillo/beta-catenin with TCFs on Wg-regulated enhancers (WREs). Split ends (Spen), a nuclear protein containing RNA recognition motifs (RRMs) and a SPOC domain, is required for optimal Wg signaling in several fly tissues. In this report, we demonstrate that Spenito (Nito), the only other fly protein containing RRMs and a SPOC domain, acts together with Spen to positively regulate Wg signaling. The partial defect in Wg signaling observed with spen RNAi was enhanced by simultaneous knockdown of nito while it was rescued by expression of nito in wing imaginal discs. In cell culture, depletion of both factors causes a greater defect in the activation of several Wg targets than RNAi of either spen or nito alone. These nuclear proteins are not required for Armadillo stabilization or the recruitment of TCF and Armadillo to a WRE. Loss of Wg target gene activation in cells depleted for spen and nito was not dependent on the transcriptional repressor Yan or Suppressor of Hairless, two previously identified targets of Spen. We propose that Spen and Nito act redundantly downstream of TCF/Armadillo to activate many Wg transcriptional targets.